Impact of Different Drying Methods on the Quality Attributes of Bilimbi (Averrhoa bilimbi l.) Fruits - Elgiriya Gamage Sanduni Sandarenu; Ganwarige Sumali Nivanthi Fernando; Kariyawasam Majuwana Gamage Menaka Menike Kariyawasam; Mahanama Geegana Gamage Awanthi (University of Sultan Ageng Tirtayasa, 2025)
Bilimbi (Averrhoa bilimbi L.), a sour tropical fruit, is underutilized but has significant export potential. Drying, a key preservation method to increase the shelf-life of the bilimbi fruits. Therefore, this study evaluated the effects of sun, dehydrator, microwave oven, and electric oven drying on the physicochemical, proximate, antioxidant, and sensory properties of bilimbi fruits. Using AOAC methods, the physical and nutritional properties were analyzed, while antioxidant activity was measured via DPPH radical scavenging, total polyphenol content, and total flavonoid content assays. Results were statistically compared using one-way ANOVA with Tukey’s test. Sensory analysis, conducted by 30 semi-trained panelists using a 7-point hedonic scale, was analyzed using the Kruskal-Wallis test. The dehydrator-dried bilimbi sample exhibited the highest rehydration ratio (3.97±0.02), crude protein (5.50±0.15%), crude fat (3.64±0.01%), and crude fiber (8.939±1.26%), along with the lowest water activity (0.48±0.002). The microwave oven-dried sample had the highest ash (17.1±3.14%), vitamin C (4.46±1.26 mg/g), and total polyphenol (71.96±1.27 mg GAE/g) content, with the lowest moisture content (5.17±0.08%). The oven-dried sample exhibited the highest DPPH radical scavenging activity (10.66±0.10 µg TE/g) and the best surface structure. Overall, dehydrator drying proved to be the best method for preserving the sensory and nutritional qualities of bilimbi fruit.